Effectiveness of exclusive self-monitoring of fasting capillary blood glucose in the treatment of diabetes - Henrique Amancio Ferreira; Gabriel Luís Silva Lima; Helena Moretti Bressane; Alessandra Cristina Pupin Silvério; Ciderleia Castro de Lima (Universidade Estadual de Maringá, 2015)
The study aims to analyze the efficacy of the exclusive self-monitoring of the fasting capillary blood glucose in the control and treatment of diabetic patients. This is a quasi-experimental study, for which five individuals with diabetes were selected, who perform only the fasting capillary blood glucose monitoring, being added about seven other measurements, a variable number according to the individual availability of the volunteer, at different times throughout the day. It was verified that four individuals presented blood glucose values by the use of the fasting capillary blood glucose monitoring, within the parameters of normality for diabetics, between 70-130 mg dL-1 of blood (ADA, 2014b), although in the other measurements, they presented values far from the ideal goal, in a significant part of the time. The study outlines a trend that shows that the glycemic monitoring values based solely on the fasting capillary blood glucose is ineffective, since they can erroneously indicate satisfactory control of the blood glucose levels. Based on the results obtained, to a more effective monitoring and which denotes levels of reliability, it is required at least three measurements of capillary blood glucose throughout the day, and also, the importance of long laboratory tests for glycemic monitoring, such as glycated hemoglobin.